Cross-ownership among firms: Some determinants of the separation of ownership from control - Klaus Ritzberger; Jamsheed Shorish (Institute for Advanced Studies (IHS), 2002)
This paper demonstrates that the current literature on cross-ownership among firms underestimates the true degree of separation between cash flow rights and voting rights. We use accounting identities to define coefficients of control, such that any (direct or indirect) control of a firm may be identified using these coefficients. This procedure is sufficient to show that under cross-ownership the voting rights associated with ownership are typically underestimated. We demonstrate by example that control and ownership of dividend rights may be entirely separated, and that multiple equilibria may exist in economies with cross ownership.
Keywords: G32; G34; 330; cross-ownership; ownership and control; corporate governance; Corporate Governance; Eigentümerstruktur; Theorie